Autonomic Cardiovascular Control in Hyperthyroid Women during Sleep. (12th December 2013) - Tobaldini, Eleonora; Pecis, Marica; Bulgheroni, Mara; Muratori, Milena; Bevilacqua, Maurizio; Montano, Nicola
Abstract : Hyperthyroidism is characterized by hyperadrenergic symptoms (i.e., tachycardia, anxiety, and increased metabolic state). Although hyperthyroid patients often complain about an impairment of sleep, no data are available on sleep characteristics and autonomic cardiovascular control during sleep in these patients. We aimed to assess sleep qualitative indices and autonomic cardiovascular regulation during sleep in hyperthyroidism (Hyperthyr) and after treatment. Six subjects with a first diagnosis of Graves' disease or hyperfunctioning nodule underwent a complete polysomnographic study (PSG) at the time of diagnosis and after the treatment, when they became euthyroid (Euthyr). ECG and respiratory signals were extracted and samples of consecutive 250–300 beats were analyzed using linear spectral and nonlinear entropy analysis of heart rate variability (HRV), during the different sleep stages. Heart rate was decreased and total power increased in Euthyr compared to Hyperthyr, both during wake and sleep; no changes of the sympathovagal balance were observed. Entropy analysis showed that regularity index was reduced in Euthyr compared to Hyperthyr, suggesting changes in the complexity of the cardiovascular control. Periodic leg movements (PLM) were reduced in Euthyr compared to Hyperthyr. In conclusion, hyperthyroidism seems to be associated with an increased sleep fragmentation, due to PLM and an altered cardiac autonomic control.